2011
DOI: 10.1063/1.3645105
|View full text |Cite
|
Sign up to set email alerts
|

Identifying structural and energetic trends in isovalent core-shell nanoalloys as a function of composition and size mismatch

Abstract: We locate the putative global minimum structures of Na x Cs 55−x and Li x Cs 55−x nanoalloys through combined empirical potential and density functional theory calculations, and compare them to the structures of 55-atom Li-Na and Na-K nanoalloys obtained in a recent paper [A. Aguado and J. M. López, J. Chem. Phys. 133, 094302 (2010)]. Alkali nanoalloys are representative of isovalent metallic mixtures with a strong tendency towards core-shell segregation, and span a wide range of size mismatches. By comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…This indicates that the formation of nanoalloys is best favored when the percentage of sodium achieves this optimal composition, and such clusters are more likely to be found in experiments. The thorough work of Aguado et al [2,21] in the 55-atom case employing density functional theory (DFT) calculations also confirms this tendency for one specific cluster size. For a visual representation, the alloys with composition that provide the lowest excess energy from 20 to 55 atoms are shown in Fig.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…This indicates that the formation of nanoalloys is best favored when the percentage of sodium achieves this optimal composition, and such clusters are more likely to be found in experiments. The thorough work of Aguado et al [2,21] in the 55-atom case employing density functional theory (DFT) calculations also confirms this tendency for one specific cluster size. For a visual representation, the alloys with composition that provide the lowest excess energy from 20 to 55 atoms are shown in Fig.…”
Section: Resultssupporting
confidence: 56%
“…5, where pentagonal pyramids and bipyramids are interspersed along the surface. For the 55-atom cluster, a thorough study has been carried out by Aguado et al [2,21], where it is shown that the icosahedral shape is assumed by pure alkaline clusters and its alloys at dilute limits. Such results were also achieved within our classical approach for pure sodium and potassium clusters, as well as for the dilute limit on the Na-rich side, where the addition of potassium atoms maintain the essential icosahedral shape up to the Na 45 K 10 , with distortions due to atom size mismatch.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, novel structures, physical properties, and processes may occur with NPs that are not observed for their bulk counterparts. [1][2][3][4] For instance, the melting point of a metallic NP is typically lower than that of the bulk metal. [5][6][7] For the metallic copper (Cu) and silver (Ag) system, it is well known that the solid solution of the binary Ag-Cu alloy is unstable, and upon heating an initially amorphous or nanocrystalline Ag-Cu alloy in bulk form will separate into Ag and Cu phases due to the large miscibility gap and positive enthalpy of mixing for this eutectic system.…”
mentioning
confidence: 99%
“…© 2014 Author (s New physical and chemical phenomena related to nanoscale effects are currently the focus of intense research. [1][2][3][4] Nanoparticles (NPs) are characterized by small volumes and a large number of surface atoms, which inherently possess a significantly larger mobility than bulk atoms. As a result, novel structures, physical properties, and processes may occur with NPs that are not observed for their bulk counterparts.…”
mentioning
confidence: 99%